Thin Layer Chromatographic studies of Some Substituted 4H-[1,4]-Benzothiazines - Ojha, K.G.; Mathur, Neha; Adwani, Purnima (Asian Journal of Chemistry, 2010)
Thin layer chromatographic methods for separation and identification are reported for some substituted 4H-[1,4]-benzothiazines developed in submicrogram amounts using silica gel plates in various nonaqueous solvent systems.